Analysis of Language Communication Strategies to Increase Voter Turnout by the Semarang City Election Commission - Bening Ageng Bumiayu (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the linguistic communication strategies deployed by the Semarang City Election Commission during the 2024 Semarang Mayoral Election across official digital platforms. Utilizing an empirical netnographic case study approach, the research systematically analyzes textual artifacts, syntactic structures, and engagement metrics gathered from the commission’s Instagram account and official website. The empirical findings reveal a structural disconnect in electoral socialization, wherein institutional outreach remains dominated by a one way, formal constative register laden with rigid legalistic terminology. Although physical turnout at polling stations achieved a fourteen year high of 71.25 percent, virtual public engagement remained stagnant, indicating that physical attendance was largely driven by candidate mobilization rather than institutional communication efficacy. To bridge this participation paradox, this paper conceptualizes the adoption of a Proactive Market Orientation through